Implementation of Information and Communication Technology in Management Learning System During the Covid 19 Pandemic - Putri, Fadia Sasabila; Dermawanis Zega (Pandawan Sejahtera Indonesia, 2023)
This study examines the use of information technology in the management system of Indonesian higher education institutions. This could have been more optimal and evenly distributed in terms of hardware and management. This study is an international journal study. Input resource findings include visualizers/document cameras, computers, whiteboards, student-ready systems, and application programs. Output resources include projectors, interactive whiteboards, and displays. monitor, television, etc. Finally, other ICT devices include digital cameras, switchers, digital recorders, and other innovations. In short, inequalities in the infrastructure supporting the application of this technology in education and the need for better preparedness of human resources for the use of information and communication technologies in learning.